Iron doped Gd2Zr2O7 hierarchical nanoflakes arrays as robust electrodes materials for energy storage application. (April 2023) - Ahmad, Shakoor; Gouadria, Soumaya; Jabbour, Karam; Naz, Asma; Manzoor, Sumaira; Abdullah, Muhammad; Ansari, Mohd Zahid; Hegazy, H.H.; Aman, Salma; Ashiq, Muhammad Naeem
Abstract: The current work highlights the use of Fe doped Gd2 Zr2 O7 electrode materials to increase the supercapacitive properties. A hydrothermal technique is used to successfully produce pure and doped Gd2 Zr2 O7 (Fe = 5 %, 10 %, and 20 %) electrode material. Fourier transform infrared (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM) along with Brunner–Emmet–Teller (BET) testing are employed for examining the crystal structure, specific surface area, morphology, and chemical composition of investigated materials. On the other hand, Fe doping altered the crystal structure and shape of the Gd2 Zr2 O7 flakes like network. Additionally, the 20 % Fe doped Gd2 Zr2 O7 electrode material acquires great specific surface area with enhanced exposed active sites of the fabricated material on the surface. On the contrary, cyclic voltammetry (CV), galvanostatic charge–discharge (GCD) & electrochemical impedance spectroscopy (EIS) is used for assessing electrochemical performance of the fabricated electrodes. According to the experimental results, 20 % Fe-doped Gd2 Zr2 O7 electrode material exhibited the best electrochemical performance, for example the specific capacitance of 2561 F g −1 at current density of 10 mV s −1 with energy density of 54 Wh kg −1 is obtained, and retention was 84 % after 30 h. Due to its high Csp as well as long durability, 20 % Fe-doped Gd2 Zr2 O7 electrode material is an excellent candidate for next-generation supercapacitor material. Highlights: Fe doped Gd2 Zr2 O7 electrode is fabricated via hydrothermal technique. Fe doping altered the crystal structure and shape of the Gd2 Zr2 O7 . 20% Fe doped Gd2 Zr2 O7 electrode material has a large specific surface area. 20% Fe-doped Gd2 Zr2 O7 shows the retention 84 % after 30 hours stability test.